Control of Anthracnose in Banana Cultivar Kolikuttu (Musa sp.) with Essential Oils and Bio-safe Fruit Coatings - P.H.I. Sanjeewani; K.O.L.C. karunanayake; L.K.R.R. Jayakody; Y.A.S. Samithri (The Open University of Sri Lanka, 2022)
Anthracnose caused by the fungus Colletotrichum musae is a widespread disease found among banana resulting in high postharvest losses in Sri Lanka. The use of essential oils (EO) to control postharvest diseases has become an ecologically friendly alternative to synthetic chemicals due to their antimicrobial properties while fruit coating is an effective method to increase shelf life. This study focused on controlling anthracnose and extending the shelf life of banana by incorporating selected EOs into a fruit coating. The gel matrix was extracted from the cortex of Aloe vera and mixed with a gelatin agent to serve as the fruit coating material. EOs was screened against C. musae which was isolated from banana cultivar Kolikuttu under in vitro bio-assay. Four different treatments were carried out under in vivo conditions. Two concentrations of gelatin (G) in 200 ml of Aloe vera (AV) coating material (2% GAV and 4% GAV) were independently mixed with the most effective EO at optimal concentration and one treatment with AV coating without EO. Untreated fruits with no EO or coating served as the control. Post-harvest quality parameters, % weight loss, total soluble solids (TSS), titratable acidity (TA), and flesh color were monitored and showed no significant undesirable effects when compared with the control. Disease severity was significantly low in coated fruits with Basil oil at 1000 µLL-1 in 2% or 4% GAV. The Most effective EO for controlling banana anthracnose was basil oil (70.28%) at 1000 µLL-1 followed by cardamom oil (53.06%). A sensory evaluation with untrained panelists showed that quality parameters were not affected by the treatments. Results indicated basil oil incorporated A. vera as a suitable bio-safe fruit coating against anthracnose in banana.